Randomized sparse block Kaczmarz as randomized dual block-coordinate descent - Petra, Stefania (Analele științifice ale Universității Ovidius Constanța. Seria Matematică, 2015)
We show that the Sparse Kaczmarz method is a particular instance of the coordinate gradient method applied to an unconstrained dual problem corresponding to a regularized l1-minimization problem subject to linear constraints.
Gesehen am 27.07.2018